2017
DOI: 10.1037/bne0000180
|View full text |Cite
|
Sign up to set email alerts
|

Age-related impairment on a forced-choice version of the Mnemonic Similarity Task.

Abstract: Previous studies from our lab have indicated that healthy older adults are impaired in their ability to mnemonically discriminate between previously viewed objects and similar lure objects in the Mnemonic Similarity Task (MST). These studies have used either old/similar/new or old/new test formats. The forced-choice test format (e.g., “Did you see object A or object A’ during the encoding phase?”) relies on different assumptions than the old/new test format (e.g., “Did you see this object during the encoding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(100 citation statements)
references
References 48 publications
16
84
0
Order By: Relevance
“…Additionally, aged rats are impaired in distinguishing the target from similar lures, but not distinct lures, which directly parallels previous findings from older adults (Toner et al, 2009;Yassa et al, 2011aYassa et al, , 2011bRyan et al, 2012;Holden et al, 2013;Stark et al, 2013Stark et al, , 2015Pidgeon and Morcom, 2014;Reagh et al, 2016Reagh et al, , 2018Huffman and Stark, 2017;Stark and Stark, 2017;Trelle et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, aged rats are impaired in distinguishing the target from similar lures, but not distinct lures, which directly parallels previous findings from older adults (Toner et al, 2009;Yassa et al, 2011aYassa et al, , 2011bRyan et al, 2012;Holden et al, 2013;Stark et al, 2013Stark et al, , 2015Pidgeon and Morcom, 2014;Reagh et al, 2016Reagh et al, , 2018Huffman and Stark, 2017;Stark and Stark, 2017;Trelle et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
“…Hippocampal contributions to the orthogonalization of similar inputs have been assessed with tasks that require discrimination of a previously viewed target image from lure images, which range in similarity to the target. These paradigms are now commonly referred to as 'mnemonic similarity' tasks (Stark et al, 2013Huffman and Stark, 2017;Stark and Stark, 2017). Functional neuroimaging studies using these tasks support earlier predictions that the ability to accurately resolve a target from similar lures is linked to activation in the DG and CA3 sub-regions of the hippocampus (Kirwan and Stark, 2007;Bakker et al, 2008;Lacy et al, 2011 p.2;Kirwan et al, 2012;Motley and Kirwan, 2012;Reagh and Yassa, 2014;Reagh et al, 2017).…”
Section: Introductionmentioning
confidence: 84%
“…This is distinct from the original mnemonic similarity tasks in which subjects are asked to judge only a single item as new or old. Critically, a recent variant of the mnemonic similarity task in which the subjects were simultaneously presented with an object from the encoding phase and a similar lure in a forced‐choice format, which is more comparable to the rat studies used here, has confirmed age‐related impairments in discriminating between similar objects (Huffman & Stark, ). Thus, the old/new and forced‐choice test formats appear to be equally sensitive to detecting age‐associated deficits.…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, the rodent work has generally used spontaneous or novel object recognition tasks that rely on rats' innate preference for novelty (Burke et al, ; Gámiz & Gallo, ), which itself is known to be compromised by aging both in humans (Daffner et al, ; Fandakova, Lindenberger, & Shing, ) and animal models (Burke, Wallace, Nematollahi, Uprety, & Barnes, ). In contrast, research in humans has used variants of the ‘mnemonic similarity task’, which tests subjects' abilities to discriminate between target and lure stimuli that vary in their distinctiveness (Huffman & Stark, ; Reagh et al, ; Ryan et al, ; Stark, Stevenson, Wu, Rutledge, & Stark, ; Stark, Yassa, Lacy, & Stark, ; Toner, Pirogovsky, Kirwan, & Gilbert, ; Yassa et al, ). The goal of the current studies was to develop and validate a rodent target‐lure discrimination task that would be comparable to the mnemonic similarity task using the Fischer 344 × Brown Norway (F344 × BN) hybrid rat model of cognitive aging.…”
Section: Introductionmentioning
confidence: 99%
“…Using modified recognition memory paradigms, such as the Mnemonic Similarity Task (MST; Stark, Yassa, Lacy, & Stark, ), MD is seen as differentially endorsing lures that are similar to, but not the same as, previously presented targets (i.e., judging lures as “new” instead of “old”). In study/test recognition paradigms, lures only appear in the separate test phase as stimuli similar to those presented during the study phase (Huffman & Stark, ; Stark, Stevenson, Wu, Rutledge, & Stark, ). In continuous recognition paradigms, similar lures and repeated targets are presented in a series with no intervening delay (Bakker et al, ; Kirwan & Stark, ).…”
Section: Introductionmentioning
confidence: 99%